Enhancing Mathematics Education with Modern Teaching Equipment in Junior Secondary Schools in Nigeria - OLASENI, Vivian Morenike,; Saziwa, Themba (Journal of Ecohumanism, 2025)
Mathematics is mainly considered a difficult subject for students, but when the teaching is simplified, assimilation becomes effortless as well. This study examined the role of modern teaching equipment in achieving mathematics education objectives in schools. Four research questions were raised to guide the study. This study aimed to see how modern technological equipment can ease the teaching and learning of Mathematics in junior secondary schools. The study employed a descriptive survey research design, focusing on Nigeria's junior secondary school mathematics teachers. A purposive sampling technique was used to select 100 teachers to participate in the study. Data were analyzed using descriptive statistics, including frequency counts and simple percentages. The findings indicated that modern teaching equipment enhances teaching by making it more engaging, improves the efficiency and effectiveness of mathematics education instructors, and highlights important aspects of learning, thus reducing rote memorization. It also facilitates school management’s access to real-time pupil and school data, strengthens the professional image of mathematics teachers, and helps maximize students’ attentiveness. However, many teachers reported challenges such as insufficient modern teaching equipment, frequent power interruptions, high costs of equipment, limited skills among teachers in using these technologies, lack of curriculum experts, and inadequate funding for teaching equipment. Despite these challenges, the use of modern teaching equipment in mathematics education is generally on the rise. Based on these findings, the study recommends that schools prioritize providing adequate ICT resources, maintain equipment properly, and employ well-qualified ICT teachers to foster the effective use of modern teaching equipment in mathematics education.